The Comparative of α- and β-Cyclodextrin as Stabilizing Agents on AuNPs and Application as Colorimetric Sensors for Fe3+ in Tap Water - Adhi Maulana Yusuf; Satrio Kuntolaksono; Agustina Sus Andreani (Indonesian Journal of Chemistry, 2023)
In this study, AuNPs were reduced using ortho-hydroxybenzoic acid (o-HBA) and various stabilizing agents (α-CDs and β-CDs). The stability, shape, size, and sensitivity of the Fe3+ detection of AuNPs α-CDs and AuNP β-CDs are compared. Both nanomaterials were characterized using ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and transmission electron microscopes (TEM). After the addition of Fe3+, the absorption rate of surface plasma resonance (SPR) increased to 524 nm, and the color of AuNPs α-CDs and AuNPs β-CDs was changed from pink to red and purple, respectively. AuNPs α-CDs are more uniform in shape and size than AuNPs β-CDs with a size of 23.34 nm. Further, AuNPs α-CDs are more stable, and the absorption rate at 524 nm wavelength decreases by 17.76%. AuNPs α-CDs have a good linear relationship with a linear regression coefficient of 0.996. The sensitivity of AuNPs α-CDs was good with LoD and LoQ both with 1.21 and 4.02 ppm, respectively. These results show that the sensor is superior in determining Fe3+. In addition, AuNPs α-CDs were used to detect Fe3+ in the tap water in South Tangerang, Banten, Indonesia.